I do the best i can: The role of immigrant parents in their children’s educational inclusion - González-Falcón, Inmaculada; Arroyo-González, María José; Berzosa-Ramos, Ignacio; Dusi, Paola (Frontiers in Education, 2022)
The research highlights the importance of immigrant parents assuming a leading and mediating role in the processes of school adjustment and their children’s educational inclusion. However, the difficulties that parents have to face as a consequence of the migration process are not always taken into account. These families have to face their own acculturation processes and reorganise their roles in the host society. This study analyses the functions that immigrant parents carry out in the new school context in order to favour the educational inclusion of their children. The analysis is approached from the parents' perspective, in order to understand the way in which families live and try to favour their children's access, participation and success at school. Ethnographic research and the use of qualitative techniques such as in-depth interviews are used. The perceptions of three immigrant fathers and seven immigrant mothers with different backgrounds and nationalities in a public school in Huelva (Andalusia, Spain) are analysed. The results point to the great fragility and difficulty experienced by these parents in exercising their parental functions in the new context. Women, especially those from Poland, Lithuania and Romania, compared to their husbands or partners, seem to suffer greater stress due to their dual role as guarantors of the culture of origin and facilitators of the host culture. In order to favour the educational inclusion of their children, parents prioritise - primarily - access to resources, but also the monitoring of their children's homework and emotional support. However, a relationship model based on cultural assimilation prevails. Among the factors that condition the behaviour of parents are their economic vulnerability, lack of knowledge of the language, limited social support, cultural differences and prejudices. The importance of the school supporting parents, and especially mothers, in their acculturation processes and their relationship with the school is underlined. In this endeavour, it is essential to count on the collaboration of different agents, such as intercultural counsellors or other parents in the school.